Comparative Study of Law Enforcement Against Taxation Crimes in Indonesia and Malaysia - Mohamed Saniff , Shereeza; Isnaini; Fithri, Beby Suryani; Iswari, S. Salini (Universitas Medan Area, 2024)
This research conducts a comparative study of law enforcement strategies aimed at combatting taxation crimes in Indonesia and Malaysia. The study examines the legal frameworks, enforcement mechanisms, and institutional capacities of tax authorities in both countries. Through an analysis of relevant laws, regulations, and enforcement practices, the research evaluates similarities and differences in approaches to tackling tax evasion, fraud, and non-compliance. Additionally, the study explores the role of collaboration between tax authorities and other government agencies, as well as international cooperation in addressing cross-border tax crimes. By identifying effective strategies and areas for improvement in law enforcement against taxation crimes, the research aims to contribute to the development of more robust and coordinated efforts to combat tax evasion and ensure compliance with tax laws in Indonesia and Malaysia.